Real‑world Outcomes and Predictors of Vision Loss after Panretinal Photocoagulation for Diabetic Retinopathy: Five‑year Follow‑up - Taufaeteau, Antonio; Bhatta, Subash; Pant, Nayana; Lopez, Valeria; Sikivou, Biu; Qoqonokana, Mundi; Naviri, Varanisese (Nepalese Journal of Ophthalmology, 2026)
Introduction: Diabetic retinopathy is a leading cause of vision loss in Fiji, where treatment options beyond panretinal photocoagulation (PRP) remain limited. In this context, evaluating longterm outcomes of PRP can provide critical insights in patient management.Objective: To evaluate real-world long-term outcomes and predictors of vision loss following PRP for severe nonproliferative diabetic retinopathy (NPDR) and proliferative diabetic retinopathy (PDR) in a resource-constrainedsetting.Methodology: Retrospective study was done using five-year follow-up data of eyes treated exclusively with PRP atthe Pacific Eye Institute, Fiji, between January 2010 and December 2015. Patients with advanced PDR, coexistingretinal pathology, or adjunctive therapies were excluded. Visual acuity, retinopathy grading, and systemic factorswere assessed. Statistical analyses included Chi-square tests, independent samples t-tests, and generalised estimating equations.Result: A total of 516 eyes (91 NPDR, 425 PDR) from 283 patients were included. At five years, 68% of PDReyes achieved stability, 19% remained active, and 13% progressed to advanced PDR. Among NPDR eyes, 17.6%progressed to active PDR and 7.7% to advanced PDR. The difference in progression between NPDR and PDR eyeswas significant at two years (p